The Relationship Between Fat and Sodium Intake and Hypertension Among Elderly Patients at Gedong Air Public Health Center in 2025 - Dwi Linasari; Asep Jalaludin; Ai Kustiani (Jurnal Kesehatan Cendikia Jenius, 2025)
Hypertension is a common non-communicable disease among the elderly and a major risk factor for heart disease, stroke, and kidney failure. The increasing number of hypertension cases among the elderly at Gedong Air Public Health Center highlights the need for research on the impact of fat and sodium intake on hypertension incidence. This study aimed to determine the relationship between fat and sodium intake and hypertension status among elderly patients at Gedong Air Public Health Center in 2025. This research employed a cross-sectional design with a quantitative observational approach. A total of 72 elderly respondents were selected using consecutive sampling. Data on fat and sodium intake were collected using the SQ-FFQ questionnaire, while blood pressure was measured using a sphygmomanometer. Data were analyzed using univariate and bivariate (Chi-square) tests. The results showed that most respondents were aged 70–79 years (44.4%), male (51.4%), and had a family history of hypertension (52.8%). A total of 63.9% of respondents had hypertension, 61.1% had insufficient fat intake, and 68.1% had high sodium intake. Bivariate analysis revealed no significant relationship between fat intake and hypertension (p=0.530), but a significant relationship between sodium intake and hypertension (p=0.013). It can be concluded that high sodium intake is associated with hypertension among the elderly. Recommended, public health education on sodium reduction is essential as a preventive effort, especially through nutritional interventions and sustainable health promotion at the primary care level.